PENGARUH EKSTRAK ETANOL DAUN SIRIH MERAH (Piper crocatum) TERHADAP GAMBARAN HISTOPATOLOGI OTOT JANTUNG TIKUS (Rattus norvegicus) DIINDUKSI ALOKSAN - Riky Alberth Lerrick; Efrisca Meliyuita Br. Damanik; Anita Lidesna Shinta Amat; Rr. Listyawati Nurina (Universitas Nusa Cendana, 2025)
Introduction: Red betel leaves (Piper crocatum) contain flavonoids, alkaloids, saponins, and tannins, which have antidiabetic properties. Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or action, leading to increased production of Reactive Oxygen Species (ROS). The antioxidants in red betel leaf extract are expected to reduce ROS formation and protect cardiac muscle from DM-induced damage.. Methods: This laboratory experimental study used a true experimental post-test only control group design. Thirty rats were divided into five groups: positive control (KK+), negative control (KK−), and treatment groups (KP1, KP2, KP3), each consisting of six rats. Histopathological features of cardiac muscle, including interstitial fibrosis, ventricular myocyte hypertrophy, and intramyocyte lipid deposits, were assessed. Data were analyzed using the Kruskal-Wallis test and Post Hoc LSD. Results: There was a significant difference in ventricular myocyte hypertrophy between groups (p = 0.009), but no significant differences were observed in interstitial fibrosis (p = 1.000) and intramyocyte lipid deposits (p = 0.866). Discussion: Red betel leaf extract at 150 mg/kg body weight effectively reduced ventricular myocyte hypertrophy in diabetic rats Conclusion: Red betel leaf extract significantly reduced ventricular myocyte hypertrophy but had no effect on fibrosis or intramyocyte lipid deposits.